Propagation of Short Electromagnetic Pulses through Nonconducting Media with Electric and Magnetic Dipole Currents - Harmuth, H.F.; Lukin, K.A. (Радиофизика и радиоастрономия, 2002)
Propagation of electromagnetic signals through a non-conducting medium with very low density of neutral gas is considered with taking into account both electric and magnetic dipole currents. A new approach based on microscopic description of the medium and analytical solution of Maxwell equations in time domain has been used to solve the problem. The time delay between the signal precursor and its main lobe evaluated may be used for evaluation of either distance to a pulsar for the known medium parameters or those parameters for a given distance to the pulsar. Распространение электромагнитных сигналов через непроводящую среду нейтрального газа с очень низкой плотностью рассмотрено с учетом электрических и магнитных дипольных токов. Для решения этой задачи использован подход, основанный на микроскопическом описании среды и аналитическом решении уравнений Максвелла во временной области. Рассчитанная задержка между предшественником и главным лепестком сигнала может использоваться для оценки либо расстояния до пульсара при известных параметрах среды, либо параметров среды для известного расстояния до пульсара. Розповсюдження електромагнітних сигналів через непровідне середовище нейтрального газу з дуже низькою густиною розглянуте з урахуванням електричних та магнітних дипольних струмів. Для розв’язання цієї задачі використано підхід, що базується на мікроскопічному опису середовища та аналітичному розв’язку рівнянь Максвелла в часовій області. Розрахована затримка між попередником та головною пелюсткою сигналу може використовуватись для оцінки або відстані до пульсара при відомих параметрах середовища, або параметрів середовища для відомої відстані до пульсара.